A LITERATURE SURVEY ON PROPOSED AFRICAN MONETARY UNIONS. (26th August 2016) - Asongu, Simplice; Nwachukwu, Jacinta; Tchamyou, Vanessa
Abstract: This study provides a survey of recent advances in the literature on proposed African monetary unions. The survey comprises about 70 empirical papers published during the past 15 years. Four main strands are discussed individually and collectively. They comprise the proposed: (i) West African Monetary Zone (WAMZ), (ii) East African Monetary Union (EAMU), (iii) Southern African Monetary Union (SAMU) and (iv) African Monetary Union (AMU). We observe a number of issues with establishing the feasibility and/or desirability of potential monetary unions, inter alia, they are variations in: choice of variables, empirical strategies, sampled countries and considered periodicities. We address this ambiguity by reviewing studies with scenarios that are consistent with Hegelian dialectics and establish selective expansion as the predominant mode of monetary integration. Some proponents make cases for strong pegs and institutions as viable alternatives to currency unions. Using cluster analysis, disaggregating panels into sub‐samples and distinguishing shocks from responses in the examination of business cycle synchronisation provide more subtle policy implications. We caution that for inquiries using the same theoretical underpinnings, variables and methods just by modifying the scope/context and periodicity may only contribute to increasing the number of conflicting findings. Authors should place more emphasis on new perspectives and approaches based on caveats of, and lessons from the European Monetary Union (EMU) and CFA zones.